Urgensi Literasi Dalam Meningkatkan Sumber Daya Manusia (Studi Kasus di SMAN 1 Puri Mojokerto) - Jaya Roza Azzukhrufi; Nugrahani Wahyu Nufitasari; Masning Khumairo (Institut Agama Islam Sumatera Barat, 2024)
The quality of human resources is closely related to literacy, literacy is related to a science obtained from information that has been obtained from reading writing or oral information, science is related to understanding and intelligence. Human resources understand the meaning of the substance of literacy can be greatly influenced by academic research, national context, institutions, cultural values, and also knowledge. UNESCO launched literacy as a country's empowerment, the advanced civilization and the rapid development of a country are indicated by the good literacy culture. The purpose of this study is to determine the urgency of literacy in improving educational human resources. This research method is qualitative by applying a case study approach. The findings of this study can be presented, that the implementation of literacy in schools is the main point of improving the quality of human resources, starting from realizing several stages, namely the habituation stage, the development stage, and the learning stage is good, then in the application of literacy culture, namely the physical environment, social and affective environment, and academic environment. This is also shown by the many achievements and student responses to social problems.